The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.17718/tojde.444640
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Reflections on Vocabulary Learning through Synchronous and Asynchronous Games and Activities

Abstract: Many learners are now quite digitally skilled. However, this does not entail that they know how to learn through digital technologies. Therefore, establishing an interactive virtual learning platform that connects everyone together in a classroom environment and helping learners become familiar with such media might serve a set of purposes in any educational setting. Today, with the advances in web-based learning technologies, a hybrid teaching methodology has become widespread: blended learning. It is a term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 24 publications
(37 reference statements)
5
36
0
2
Order By: Relevance
“…On the whole, the positive perceptions of students toward gamified quizzing in the present study confirm the findings of a number of studies that reported positive perceptions of students toward gamification and gamified applications (Cheong, Filippou, & Cheong, 2014;Stanley, 2014;Dizon, 2016;Zarzycka-Piskorz, 2016;Rajšp, et al, 2017;Yildirim, 2017;Ab. Rahman, et al, 2018;Bicen & Kocakoyun, 2018;Karaaslan et al, 2018;Ortega-Arranz et al, 2019). Regarding the effect of music on students' perceptions toward Kahoot gamified quizzing, the results of the present study, especially those on perceived usefulness, partly agree with the findings of Wang and Lieberoth (2016) who concluded in their study that music and points had no significant effect on students' perceived learning.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…On the whole, the positive perceptions of students toward gamified quizzing in the present study confirm the findings of a number of studies that reported positive perceptions of students toward gamification and gamified applications (Cheong, Filippou, & Cheong, 2014;Stanley, 2014;Dizon, 2016;Zarzycka-Piskorz, 2016;Rajšp, et al, 2017;Yildirim, 2017;Ab. Rahman, et al, 2018;Bicen & Kocakoyun, 2018;Karaaslan et al, 2018;Ortega-Arranz et al, 2019). Regarding the effect of music on students' perceptions toward Kahoot gamified quizzing, the results of the present study, especially those on perceived usefulness, partly agree with the findings of Wang and Lieberoth (2016) who concluded in their study that music and points had no significant effect on students' perceived learning.…”
Section: Discussionsupporting
confidence: 89%
“…Research has indicated that using applications that inject game elements (such as music, colors, bonuses, feedback, countdown timer, leaderboards, and points) into learning content help students learn and improve their language skills. To begin with, a number of recent studies suggested that these technologies enhance intrinsic motivation and help students learn grammar more effectively than other traditional language teaching approaches (Zarzycka-Piskorz, 2016;Karaaslan, Kilic, Guven-Yalcin, and Gullu, 2018). Similarly, it has been demonstrated that using these tools contribute significantly to students' learning of English vocabulary (Dizon, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For this summary, the number of games was analyzed instead of the number of papers. Considering that some authors such as Zhonggen [82] and Karaaslan [67] used multiple games, the total number of games was higher than the number of papers (n = 119). Additionally, three papers were omitted because they did not explicitly test or observe language skills or performed tests that were not fully explained.…”
Section: Are There Differences Between Bespoke and Off-the-shelf Games Regarding Their Impact On Observed Outcomes Within A Specific Age mentioning
confidence: 96%
“…Interactive Teaching is an attempt to project and construct the image of modern teacher, trying to answer the challenges of time. In a methodological sense it is a quest for better teaching techniques and learning outcomes (Hanghøj, Lieberoth, & Misfeldt, 2018;Karaaslan, Kilic, & Guven-Yalcin, 2018;Tikhomirova, Bogatyrev, & Bogatyreva, 2018). From a linguistic standpoint Interactive Teaching modern foreign languages is perceived as another attempt to construe "Language in Action".…”
Section: Professional Culture and The Concept Of Teacher Are Undergoimentioning
confidence: 99%